Epithelial Wound Healing on Keratin Film, Amniotic Membrane and Polystyrene In Vitro. (8th January 2014) - Feng, Yaqing; Borrelli, Maria; Meyer-ter-Vehn, Tobias; Reichl, Stephan; Schrader, Stefan; Geerling, Gerd
Abstract: Purpose : Corneal epithelial wound healing is a major issue in ocular surface (OS) reconstruction. Aim of this study was to evaluate parameters of epithelial wound healing in vitro on transparent keratin films (KFs) derived from human hair in comparison with amniotic membrane (AM) and polystyrene. Materials and Methods : The human corneal epithelial cell line (HCE-T) was expanded on KF, AM and commercially available 24-well polystyrene cell culture plates in vitro to compare cell proliferation, migration and attachment by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide, scratch-wound healing and adhesion assay. Cells cultured on KF and AM at an air–liquid interface for 14 d were stained with hematoxylin and eosin for histology. Results : The highest proliferation of HCE-T cells was observed on polystyrene at all time points ( p < 0.05). At a seeding density of 5 × 10 3 cells/well, no difference in proliferation was found between AM and KF after 24 h and 72 h ( p = 0.582 and p = 0.066), while higher proliferation was observed on AM compared to KF after 48 h ( p = 0.005). At a seeding density of 1 × 10 4 cells/well, no difference was found between AM and KF after 24 h ( p = 0.252), while higher proliferation was observed on AM compared to KF after 48 h and 72 h ( p = 0.001 and p = 0.003). The significantly fastest cell migration was observed on polystyrene at all time points ( p < 0.01). Cell migration was significantly higher on KF compared to AM at 48 h ( p < 0.05). After 30 min, there were significantly more cells attached to AM compared to polystyrene and KF ( p = 0.032 and p = 0.001). No significant difference in cell attachment was observed between KF and polystyrene ( p = 0.147). Histology demonstrated that HCE-T cells cultured on KF and AM at an air–liquid interface for 14 d form a multilayered epithelium similar to normal human corneal epithelium. Conclusion : Transparent KFs derived from human hair support proliferation, migration, adhesion and differentiation of HCE-T cells in vitro . Therefore, it could be a promising alternative to AM for OS reconstruction.